Formulation and Evaluation of Controlled Release Tablet of Lamotrigine: Formulation and Evaluation of Controlled Release Tablet of Lamotrigine - Vishwakarma, Swati (International Journal of Pharmaceutical & Biological Archive, 2018)
Controlled drug delivery [16] can be defined as delivery of the drug at a predetermined rate and/or to a location according to the needs of the body and disease states for a definite time period. Controlled release drug administration means not only the prolongation of the duration of drug delivery, similar to the objective in sustained release and prolonged release, but the term also implies the predictability and reproducibility of drug release kinetics. Oral controlled release drug delivery system is one that provides continuous oral delivery of drugs at predictable and reproducible kinetics for a pre-determined period throughout the course of GI transit.